High-level petri nets control modules for service-oriented devices: a case study - Mendes, João M. (2009)
This paper describes a solution for the control of service-oriented devices based on modular and special adapted High-Level Petri Nets process description of intra- and intercontrol activities. The procedure is applied on a case study scenario, corresponding to a real transfer system made of several control devices represented as service-oriented components able to share information between them. The High-Level Petri Nets are adapted to associable models applicable to describe control processes and sufficient elastic for different control strategies. Valuable and flexible control features are obtained from its application, such as an integrated methodology for the modular control with decision support and validation.